Decentralization in Lesotho: prospects and challenges - Daemane, Moses M.M. (My University, 2012)
Developing countries are marred with non-development delivery and rural and urban poverty. The largest section of the rural poor population is often involved in subsistence farming while the urban poor are involved in cyclic poverty in the informal sector. There is a need therefore, for good local governance that is responsive to the needs of the rural and urban citizens, particularly the poor. Good local governance ensures that everyone regardless of status, gender, race, age or religion, is enabled to participate productively and positively in the opportunities available. Stren (2005) emphasizes that social inclusiveness is an important goal for local governance as it is just, democratic and productive. Social inclusion is central to sustainable rural and urban development. Development thinking is also increasingly stressing the importance of human capital, that is, the important contributions all people including the poor, can make to development. Decentralization has, furthermore, focused attention on the local level, as good entry point for addressing wide range of social issues including poverty but particularly lack of local development-services delivery. Hence, this proposed study centres on good local governance and participation of the poor in the rural and urban areas in Lesotho as some pre-requisites for sustainable human development and development-services delivery particularly for the rural subsistence farmers, the landless and the urban poor. Lesotho’s local government was mainly created to meet the needs of Lesotho citizens and reduce poverty through more focussed development delivery and local democratization. This thesis examines the evolution of Lesotho local governance, the manner in which it has (and the degree to which it has actually) been adopted, as well as its effectiveness in local developmental-service delivery and implications towards rural and urban sustainable development. The key question is whether ‘developmental local governance’ (DLG) in Lesotho precipitates adequate social inclusion of the rural and urban poor to the point of real developmental-service delivery and community driven development. On the basis of secondary and primary data, beneficiary assessment and in-depth interviews/participatory evaluation, the thesis argues that local governance has been largely unsuccessful in meeting these objectives. The thesis argues that, in large part, this is due to locally lacking preconditions for successful decentralization and the prevailing institutional constraints against it. However, the thesis believes that such an impasse of non-developmental-service delivery locally can only be surmountable through adequate social inclusion, fiscal-administrativepolitical devolution, setting and meeting of the necessary preconditions for successful decentralization and effective tackling of the concerned current analyzed institutional constraints for relevant and sustainable development locally. Good local governance without pragmatic social inclusion of the rural and urban poor is a recipe for intense rural and urban poverty. The proposed thesis assumes that social inclusion which is non-isolation or non-exclusion from the social development process, employment opportunities, the economy, mainstream political and cultural processes, security net-works and non-vulnerability, is central to sustainable rural and urban development and development delivery. Organized, logical and sound chapters at the pragmatic, various theoretical and policy levels have been utilized to construct this thesis. With a view to juxtapose the implicit and explicit institutional constraints to DLG, the global and peculiar evolutionary process of DLG embracing general and relevant examples and Lesotho in particular as a case study are covered.
PH.D. University of the Witwaterserand, Faculty of Humanities (Development Studies), 2012